Superman : Superman versus Bizarro - Strathearn, Chris; MADA Design, Inc. (New York : Harper, 2010)
Bizarro, Superman's backward clone, tries to help with several emergencies in Metropolis, but his efforts only make the situations worse and Superman has to convice him to return to his own world where he is considered a hero.
Keywords: Superheroes -- Fiction; Adventure and adventurers -- Fiction; Superheroes -- Fiction; Adventure fiction